Impacts of adding pectic polysaccharides from Hassawi okra extract (Abelmoschus esculentus) on quality properties of strawberry jam - Nashi K. Alqahtani; Tareq M. Alnemr; Zakaria A. Salih; Hassan T. Aboufarrag (Journal of Agriculture and Food Research)
Okra mucilage is well known source of pectic polysaccharides. However, it has not been used as gelling agent in jam processing. With the increased demand for cheap and natural alternatives of pectin, the current study investigated the effect of aqueous okra extract from Hassawi variety as a source of fiber and polysaccharide to mitigate the reduction of pectin level on physicochemical and quality parameters of strawberry jam. A fixed amount of okra extract was added while pectin level was reduced by 25, 50, 75 and 100 %. The results revealed that the reduction of pectin in the presence of okra extract did not significantly affect the moisture content, TSS, aw, pH and acidity of jam samples (p ≤ 0.05). There was a decrease in the hardness, adhesiveness, springiness, gumminess and chewiness, while the cohesiveness increased with pectin reduction. However, the addition of okra extract mitigated the effect of moderate reduction of pectin on texture profile as no significant differences were observed for samples with 25 and 50 % pectin reduction compared to the control (p ≤ 0.05). The treatments did not affect the color parameters except for the yellowness (b∗) which increased significantly from 0.23 to about 0.45 as a result of okra extract presence (p ≤ 0.05). The sensory evaluation showed that all samples had suitable acceptability and samples produced with 25 and 50 % pectin reduction and okra extract exhibited non-significant different sensory attributes compared to the control (p ≤ 0.05). Okra extract lessen the effect of pectin reduction on microstructure of jam with minimal observed changes in samples with moderate reduction level of pectin. The results showed the usefulness of okra extract as a pectin substitute.